2002
DOI: 10.1007/s00125-001-0767-4
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine pancreas development is altered in foetuses from rats previously showing intra-uterine growth retardation in response to malnutrition

Abstract: Early malnutrition decreases beta-cell mass in the first generation of offspring and impairs the subsequent beta-cell adaptation to pregnancy. The beta-cell alteration is also present in the next generation and involves a decreased expansion of the epithelial population expressing Pdx-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 11 publications
5
44
0
1
Order By: Relevance
“…This beta-cell alteration was also present in the next generation [91]. Glucose metabolism was shown to be altered in the adequately nourished offspring of the offspring of rats malnourished (LPD) during gestation and perinatal life, demonstrating the persistence of the effects in the third generation [89].…”
Section: Effects Present In the F1 Persisting To The F2 And Beyondmentioning
confidence: 89%
“…This beta-cell alteration was also present in the next generation [91]. Glucose metabolism was shown to be altered in the adequately nourished offspring of the offspring of rats malnourished (LPD) during gestation and perinatal life, demonstrating the persistence of the effects in the third generation [89].…”
Section: Effects Present In the F1 Persisting To The F2 And Beyondmentioning
confidence: 89%
“…Stanger et al (2007) demonstrated that selective genetic reduction in the size of Pdx1+ pancreatic progenitors during the fetal period results in impaired beta-cell formation during the postnatal period with consequent development of glucose intolerance during adulthood. Consistent with this, maternal food restriction leads to significant reduction in Pdx1+ and Ngn3+ (Neurogenin 3) pancreatic precursors during embryonic development in rats, decreased postnatal beta-cell formation, and inability to expand beta-cell mass in response to pregnancy (Garofano et al, 1998;Blondeau et al, 2002). Another mechanism proposed to explain reduced beta-cell formation after IUGR is related to prenatal glucocorticoid exposure.…”
Section: Molecular Mechanisms Mediating the Perinatal Beta-cell Adaptmentioning
confidence: 58%
“…Therefore, intergenerational progression of glucose intolerance can derive from both the maternal and paternal lines. This is an experimental proof that transgenerational transmission of IGT may also occur through the paternal lineage, besides the more widely accepted maternal and grand maternal inheritance of diabetes (Zambrano et al, 2005;Drake et al, 2005;Blondeau et al, 2002;Benyshek et al, 2006). Conceptually, transgenerational inheritance of disease risk may be mediated by nongenomic mechanisms, including either 1) epigenetic mechanisms (Ozanne & Constancia, 2007;Pinney & Simmons, 2009;Drake & Liu, 2009;Waterland & Michels, 2007) or 2) other broader indirect mechanisms associated with parental physiology (Gluckman et al, 2007).…”
Section: Transgenerational Inheritance Of Beta-cell Mass Programmingmentioning
confidence: 79%
See 1 more Smart Citation
“…1a). In addition to the paradigm of gestational diabetes, many other examples show the inheritance of diabetic phenotypes through the maternal lineage (35)(36)(37)(38)(39) . The transfer of phenotypic information through the maternal lineage is based on a complex interplay of several mechanisms, including genetics, epigenetics, mitochondrial DNA transfer, the in utero environment and, in human subjects, culture and behaviour (33) .…”
Section: Maternal V Paternal Effectsmentioning
confidence: 99%